Transformasi Pembelajaran Digital Inklusif Berbasis RS-BPBL© EduLink pada Anak Yatim Piatu Duafa Binaan Masjid: Model Masjid EduTech - Wahyudi, Wahyudi; Karfindo, Karfindo; Meta, Monanda Rio; Zakki, Aulia Ahmad; Ajwari, Ridwan (Forum Kerjasama Pendidikan Tinggi, 2025)
The digital divide among underprivileged orphaned children (AYPD) remains a key barrier to inclusive education. This community service program aimed to improve digital literacy, independent learning, and social participation of AYPD through the implementation of RS-BPBL© EduLink, positioning the mosque as a community learning hub. The program was conducted at Masjid As-Salaam, Padang, in five stages: socialization, training, technology implementation, mentoring, and sustainability. Evaluation was carried out through pre–post tests, activity logs, and showcase products. The results demonstrated significant improvements in knowledge (84.5%) and digital skills (85.7%), full adoption of the LMS (100% of participants), and 85% successfully managing independent study schedules for 6 weeks. Three showcases were conducted as authentic assessments that fostered reflection and social accountability. The program confirmed the effectiveness of the Masjid EduTech model in bridging the digital divide while strengthening community-based learning ecosystems. This initiative holds strong replication potential in other communities and aligns with SDG 4 (Quality Education), Asta Cita (human capital development), and Indonesia’s higher education strategic agenda.